Construction of the Finnish Army in World War II Database - Ilari Taskinen (Historical Life Course Studies)
This article introduces the Finnish Army in World War II Database (FA2W) currently under construction that is being built to study the effects of World War II on Finnish society. The database is a stratified sample of 4,253 representative of the men who served in the Finnish Army in World War II. The data have been gathered from the military service record collection of the Finnish Army, which holds files on practically all draft-age Finnish men of the birth cohort 1903–1926 and around 70% of the birth cohorts 1897–1902. The amount of data is extensive, containing over 60 different variables. The main part of the database consists of men's military careers, comprising longitudinal data on their positions in society and in the army (e.g., civilian/conscript/frontline service), military unit, military branch, task, rank, and service class. Other information includes socio-economic information from the draft and wartime and war experiences, such as wounds, illnesses, medical treatments, death, and honors. In the future the database will be expanded with men’s postwar life trajectories to study the long-term effects of the war.